Litophellia enoplosa sp. nov., a new species of sea anemone (Actiniaria, Metridioidea) from cold-water coral environments in the North-western Mediterranean Sea - RODRÍGUEZ, ESTEFANIA; COLLINS, SOPHIA; GRINYO, JORDI; PUIG, PERE (Mediterranean Marine Science, 2023)
A new species of sea anemone (Actiniaria, Metridioidea) is described and illustrated from cold-water coral environments at 600 m depth at the Blanes Canyon in the north-western Mediterranean Sea. Litophellia enoplosa sp. nov. is characterized by a column divisible into scapus and scapulus, the former with cuticle forming tenaculi, a mesogleal marginal sphincter muscle, more mesenteries proximally than distally arranged octomerously, and a single pair of directive mesenteries; it has strong retractor and parietobasilar muscles, and acontia with basitrichs and p-mastigophores B2a. Litophellia enoplosa sp. nov. is the second species described in the genus and it can be distinguished from the other species by the cuticle in the column, size ranges of the cnidae, and geographic and bathymetric distribution.